2009
DOI: 10.1186/bf03353174
|View full text |Cite
|
Sign up to set email alerts
|

Co-seismic and post-seismic pore-fluid pressure changes in the Philippine Sea plate and Nankai decollement in response to a seismogenic strain event off Kii Peninsula, Japan

Abstract: New pressure data from a pair of Ocean Drilling Program (ODP) hydrologic borehole observatories at ODP Sites 1173 and 808, located off Japan in the subducting Philippine Sea plate and in the nearby Nankai accretionary prism, respectively, show clear signals associated with an earthquake swarm off the Kii Peninsula that began on September 5, 2004, roughly 220 km away from the observatory sites. At Site 1173, formation pressures rose by 1.0-1.5 kPa at the time of the largest earthquake (M w = 7.5), then continue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 27 publications
3
26
0
Order By: Relevance
“…More recently, it has been demonstrated that APGs can resolve centimeter-level deformation during offshore slow slip events [Ito et al, 2013;Davis et al, 2015;Wallace et al, 2016]. APG data also show changes in formation pore pressure when used as part of borehole observatories and provide a sensitive measure of volumetric strain during earthquakes and other transient deformation events, as well as responses to other forcing processes, including ocean tidal loading and hydrologic perturbations [e.g., Wang and Davis, 1996;Screaton et al, 2000;Sawyer et al, 2008;Davis et al, 2009].…”
Section: Deformation Models From Seafloor and Borehole Pressure Changesmentioning
confidence: 99%
“…More recently, it has been demonstrated that APGs can resolve centimeter-level deformation during offshore slow slip events [Ito et al, 2013;Davis et al, 2015;Wallace et al, 2016]. APG data also show changes in formation pore pressure when used as part of borehole observatories and provide a sensitive measure of volumetric strain during earthquakes and other transient deformation events, as well as responses to other forcing processes, including ocean tidal loading and hydrologic perturbations [e.g., Wang and Davis, 1996;Screaton et al, 2000;Sawyer et al, 2008;Davis et al, 2009].…”
Section: Deformation Models From Seafloor and Borehole Pressure Changesmentioning
confidence: 99%
“…The absence of anomalous flow signals at sites further landward supports the conclusion that the slow slip event initiated in the shallow part of the subduction zone without any triggering from a nearby seismic or aseismic event such as in the seismogenic zone further downdip. Like the hypothesized 2003 slow slip event on the shallow decollement off Nankai's Cape Muroto that produced pressure anomalies and caused VLF events [ Davis et al , 2006] and a similar event off the nearby Kii Peninsula in 2004 [ Obara and Ito , 2005, Davis et al , 2009], this Costa Rica slow slip event cannot be explained using a simple subduction fault model with zones that are strictly stable sliding or stick slip. Instead, the inferred transient slow slip event during the interseismic period suggests complex dynamic behavior in the frontal prism.…”
Section: Discussionmentioning
confidence: 95%
“…The volumetric strain that results from a deformation event, either seismogenic or aseismic, causes a change in pore pressure. Seafloor borehole observatories monitoring pore pressure in the Nankai prism off Japan recorded two anomalous pressure events coincident with very low frequency earthquakes in the shallow subduction zone off Cape Muroto (2003 event) and the Kii Peninsula (2004 event) [ Obara and Ito , 2005; Davis et al , 2006; Ito and Obara , 2006; Davis et al , 2009]. These events, indicative of transient deformation updip of the seismogenic zone, were not preceded or accompanied by any “normal” seismic activity, suggesting a mechanism exists that allows for initiation of shallow slip transience without triggering by a deeper seismic event.…”
Section: Introductionmentioning
confidence: 99%
“…Key foci for post-expedition studies on core samples and downhole logging data include but are not limited to • Structural analyses to characterize deformation mechanisms and style and fracture and fault orientations (e.g., Byrne et al, 2009); • Analysis of wellbore failures (breakouts and tensile fractures) to characterize contemporary maximum and minimum stress orientations and, with constraints on rock strength, potentially constrain absolute stress magnitudes; • Laboratory measurements of fault and wall rock rheology to test hypotheses linking fault constitutive properties to slip behavior (e.g., Saffer and Wallace, 2015;Leeman et al, 2016); • Geomechanical and thermal properties measurements to define poroelastic, strength, and heat transport properties of the formation and to guide interpretation of observatory data (e.g., Wang, 2004;Sawyer et al, 2008;Davis et al, 2009;Kinoshita et al, 2018); and • Strength, permeability, and elastic moduli measurements to provide context for the interpretation of borehole failures as indicators of in situ stress magnitude, parameterization of deformation and hydrologic models, and core-log-seismic integration.…”
Section: Background and Objectivesmentioning
confidence: 99%